La arquitectura religiosa del siglo XX en Latinoamérica. Dos enfoques posibles. - Fernández-Cobián, Esteban (Revista: Módulo Arquitectura CUC)
When, during the 20th century, Latin America began to manifest its own identity to the world, architecture was able to echo many of its most characteristic features. This article visits recent Latin American religious architecture -a subject that has not yet been studied as a whole-taking as a reference two elements of analysis: the artistic and technological criterion -perhaps the most usual approach in architectural histories written by architects- and the linking of architecture with other human sciences, such as geography, sociology, theology or even politics, a point of view that has so far not been applied on this continent.